Effects of Ciprofloxacin-containing Scaffolds on Enterococcus faecalis Biofilms - Albuquerque, Maria T. P. [UNESP]; Valera, Marcia C. [UNESP]; Moreira, Camila S. [UNESP]; Bresciani, Eduardo [UNESP]; Melo, Renata M. de [UNESP]; Bottino, Marco C. (Elsevier B.V., 2015)
Introduction: Antibiotic-containing polymer-based nanofibers (hereafter referred to as scaffolds) have demonstrated great potential for their use in regenerative endodontics from both an antimicrobial and cytocompatibility perspective. This study sought to evaluate in vitro the effects of ciprofloxacin (CIP)-containing polymer scaffolds against Enterococcus faecalis biofilms. Methods: Human mandibular incisors were longitudinally sectioned to prepare radicular dentin specimens. Sterile dentin specimens were distributed in 24-well plates and inoculated with E. faecalisfor biofilm formation. Infected dentin specimens were exposed to 3 groups of scaffolds, namely polydioxanone (PDS) (control), PDS + 5 wt% CIP, and PDS + 25 wt% CIP for 2 days. Colony-forming units (CFU/mL) (n = 10) and scanning electron microscopy (SEM) (n -= 2) were performed to quantitatively and qualitatively assess the antimicrobial effectiveness, respectively. Results: PDS scaffold containing CIP at 25 wt% showed maximum bacteria elimination with no microbial growth, differing statistically (P < .05) from the control (PDS) and from PDS scaffold containing CIP at 5 wt%. Statistical differences (P < .05) were also seen for the CFU/mL data between pure PDS (5.92-6.02 log CFU/mL) and the PDS scaffold containing CIP at 5 wt% (5.39 5.87 log CFU/mL). SEM images revealed a greater concentration of bacteria on the middle third of the dentin specimen. after 5 days of biofilm formation. On scaffold exposures, SEM images showed similar results when compared with the CFU/mL data. Dentin specimens exposed to PDS + 25 wt% CIP scaffolds displayed a practically bacteria-free surface. Conclusions: On the basis of the data presented, newly developed antibiotic-containing electrospun scaffolds hold promise as an intracanal medicament to eliminate biofilm/infection before regenerative procedures.
Keywords: Antibiotic; bacteria; disinfection; electrospinning; nanofibers; pulp; regeneration; root canal; scaffold; stem cells